The Role of Sustainability Accounting in Enhancing Stakeholder Trust and Transparency - Purwanti, Ari; Pamungkas, Eko Wiji; Kartikaningrum, Sari; Ng, Suwandi; Nurcahaya, Claudya (Dinasti Publisher, 2025)
Sustainability accounting goes beyond the traditional financial reporting framework by encompassing non-financial information that significantly affects long-term business performance and societal welfare. This study employs a Literature Review methodology to critically analyze existing research on sustainability accounting's role in enhancing stakeholder trust and transparency. The literature review on